Using dickey _ fuller expanded test for testing variables of investment function in Iraq - فرحان, عقيل حميد (Journal of Economics and Administrative Sciences, 2019)
To ascertain the stability or instability of time series, three versions of the model proposed by Dickie-Voller were used in this paper. The aim of this study is to explain the extent of the impact of some economic variables such as the supply of money, gross domestic product, national income, after reaching the stability of these variables. The results show that the variable money supply, the GDP variable, and the exchange rate variable were all stable at the level of the first difference in the time series. This means that the series is an integrated first-class series. Hence, the gross fixed capital formation variable, the variable national income, and the variable interest rate are stable at the time series level. Which means that the series is a complete zero-grade. In this study, it is found that most of these variables are unstable in time series but stable in the first difference. It is also concluded that the contribution of the independent variable (money supply) in the investment becomes negative.